Relationship of Maternal Hemoglobin and the Intergenic Period with Birth Weight - Carlos Alberto Llerena Gómez; Evelyn Carolina Betancourt Rubio; Karen Aracelly Tobar Almendariz (Medisur)
Foundation: birth weight constitutes one of the valuable aspects to outline maternal and child health actions and assess prenatal care. Objective: determine the relationship between maternal hemoglobin and the intergenic period with the baby's birth weight. Method: a descriptive and cross-sectional study was carried out on pregnant women treated at a hospital of the Ecuadorian Social Security Institute during the first semester of 2023. The study population was made up of the 305 pregnant women who received care in the first semester of 2023. The sample It corresponded to the total population. To determine the relationship between the variables, Pearson's correlation was used. Results: the neonates of 81 of the pregnant women had low birth weight. The mean hemoglobin in pregnant women with children with low birth weight was 11.65 ± 1.68 mg/dl and the birth interval were 24.56 ± 15.64 months. In those whose children did not have low birth weight, the mean hemoglobin was 13.72 ± 2.01 mg/dl and the birth interval were 44.71 ± 14.93 months. A statistically significant positive correlation (r = 0.665; p < 0.001) was identified between maternal hemoglobin, interpregnancy interval (r = 0.527; p < 0.05) and newborn weight. Conclusions: factors such as maternal hemoglobin during pregnancy and the duration of the intergenic period influence birth weight. The presence of maternal anemia and a short birth period are related to low birth weight.